Mediterranean Diet attenuates risk of frailty and sarcopenia: New insights and future directions. Issue 2 (1st July 2017) - McClure, Rebecca; Villani, Anthony
Abstract: Sarcopenia and physical frailty are associated with progressive disability and predictive of negative health outcomes. Dietary interventions are considered the cornerstone in the management of sarcopenic symptomology and physical frailty. However few studies have investigated preventative strategies. Moreover, most studies have focused on the efficacy of individual nutrients or supplements rather than dietary patterns. The Mediterranean Diet (MedDiet) is a dietary pattern that provides evidence for an association between diet quality, healthy ageing and disease prevention. The purpose of this paper was to examine, synthesise and develop a narrative review of the current literature, investigating the potential benefits associated with adherence to a MedDiet and attenuation of physical frailty and sarcopenic symptomology in older adults. We also explored the underlying mechanisms underpinning the potential benefits of the MedDiet on ameliorating physical frailty and sarcopenic symptomology. Synthesis of the reviewed literature is suggestive of a decreased risk of physical frailty and sarcopenic symptomology with greater adherence to a MedDiet. We identified the anti‐inflammatory and high antioxidant components of the MedDiet as two potential biological mechanisms involved. Due to a lack of evidence from RCTs to support the proposed physiological mechanisms, we suggest investigating these observations in older adults with type 2 diabetes (T2DM) whom are vulnerable to physical frailty and disability. A number of biological mechanisms describing the pathway to disability in older adults with T2DM have been postulated with many of these mechanisms potentially mitigated with dietary interventions involving the MedDiet. Exploring these mechanisms with the use of well‐designed, longer‐term dietary intervention studies in older adults with an increased vulnerability to physical frailty and sarcopenia is warranted.